1-Octyl-2-(octylthio)-1H-benzimidazole as a new and Effective Corrosion Inhibitor for Carbon Steel in 1 M HCl - El-Hajjaji,F. (2019)
The corrosion inhibition effect of 1-octyl-2-(octylthio)-1H-benzimidazole (T3) on mild steel in a 1 M hydrochloric acid solution was studied using weight loss measurement, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques, at 308 K. This compound has exhibited a corrosion inhibition efficiency of 93% at 10-3 M concentration. The adsorption of this molecule onto the mild steel surface obeyed Langmuir adsorption isotherm. Potentiodynamic polarization measurements indicated that the studied compound acted as a mixed type corrosion inhibitor. EIS results showed that an increased inhibitor concentration led to an increase in the polarization resistance and decrease in the double layer capacitance.